Quantum effects in cryocrystals in a wide temperature range - Leont’eva, A.; Prokhorov, A.; Romanusha, V.; Efimov, V. (Физика низких температур, 2019)
Due to the ever-increasing interest in cryocrystals in scientific and applied problems, a thorough study of their
various properties and characteristics is necessary. The analysis of experimental anomalies in a number of physical properties of quantum cryocrystals (helium, hydrogen and methane) is presented in the low-temperature region. In this temperature region thermal fluctuations decrease sharply, whereas the role of quantum fluctuations
stays dominant. This is manifested not only in the translational motion of atoms or defects in such crystals (as
helium, neon), but also in the rotational degrees of freedom, for example, in the properties of solid methane and
hydrogen. У зв’язку з постійно зростаючим інтересом до кріокристалів у наукових та прикладних задачах необхідно ретельне
вивчення їх різних властивостей і характеристик. Наведено
аналіз експериментальних аномалій ряду фізичних властивостей квантових кріокристалів (гелій, водень, метан) в області
низьких температур, де термічні флуктуації різко зменшуються, а роль квантових флуктуацій стає домінуючою. Це
проявляється не тільки в поступальному русі атомів або дефектів в таких кріокристалах, як гелій і неон, але й в обертальних ступенях свободи, наприклад, твердого метану та
водню. В связи с постоянно растущим интересом к криокристаллам в научных и прикладных задачах необходимо тщательное
изучение их различных свойств и характеристик. Представлен анализ экспериментальных аномалий ряда физических
свойств квантовых криокристаллов (гелий, водород, метан) в
области низких температур, где термические флуктуации
резко уменьшаются, а роль квантовых флуктуаций становится доминирующей. Это проявляется не только в поступательном движении атомов или дефектов в таких криокристаллах, как гелий и неон, но и во вращательных степенях
свободы, например, твердого метана и водорода.